Nonoperative treatment of infantile spinal deformity. Issue 5 (September 2018) - Roye, Benjamin D.; Vitale, Michael
Abstract : Progressive infantile scoliosis is one of the more challenging problems faced by pediatric spinal deformity surgeons. These curves can be rapidly progressive and lead to significant respiratory compromise. Moreover, surgical options are fraught with complications. There has been a widening role for casting in this population over the past 10-15 yr with encouraging outcomes. The literature of the last few years has reinforced evidence that casting works best in younger patients (<2 yr old) with smaller, idiopathic curve types. There also is expanded evidence for the use of casting to delay surgery when curve resolution does not seem to be a realistic expectation. Studies have also demonstrated the role of increased body mass index in predicting better outcomes in idiopathic infantile patients and have examined how reduced vertebral body wedging improves the likelihood of maintaining curve correction after casting. In sum, these findings confirm that casting is an effective intervention and outline some new variables that can predict successful outcomes both before and after cast treatment.